Expanding new chemistry of aza-boracyclophanes with unique dipolar structures, AIE and redox-active open-shell characteristics. Issue 39 (28th September 2022) - Jia, Yawei; Li, Pengfei; Liu, Kanglei; Li, Chenglong; Liu, Meiyan; Di, Jiaqi; Wang, Nan; Yin, Xiaodong; Zhang, Niu; Chen, Pangkuan
Abstract : We have achieved the synthesis of new B/N doped macrocycles by stitching oligoarylamine pentamers using arylborane acceptor segments. They exhibit open-shell radical species and AIE under ambient conditions. Abstract : π-Conjugated macrocycles involving electron-deficient boron species have received increasing attention due to their intriguing tunable optoelectronic properties. However, most of the reported B(sp 2 )-doped macrocycles are difficult to modify due to the synthetic challenge, which limits their further applications. Motivated by the research of non-strained hexameric bora- and aza-cyclophanes, we describe a new class of analogues MC-BN5 and MC-ABN5 that contain charge-reversed triarylborane (Ar3 B) units and oligomeric triarylamines (Ar3 N) in the cyclics. As predicted by DFT computations, the unique orientation of the donor–acceptor systems leads to an increased dipole moment compared with highly symmetric macrocycles (M1, M2 and M3 ), which was experimentally represented by a significant solvatochromic effect with large Stokes shifts up to 12 318 cm −1 . Such a ring-structured design also allows the easy peripheral modification of aza-boracyclophanes with tetraphenylethenyl (TPE) groups, giving rise to a change in the luminescence mechanism from aggregation-caused quenching (ACQ) in MC-BN5 to aggregation-induced emission (AIE) in MC-ABN5 . The open-shell characteristics have been chemically enabled and were characterized by UV-Vis-NIR spectroscopy and electron paramagnetic resonance (EPR) for MC-BN5 . The present study not only showed new electronic properties, but also could expand the research of B/N doped macrocycles into the future scope of supramolecular chemistry, as demonstrated in the accessible functionalization of ring systems.